The Role of The Influence of Fund Withdrawal Plan and Human Resources Competency on Budget Performance Mediated by Budget Absorption - Ariyati, Ariyati; Rahmawati, Farida; Prananta, Widya (Universitas Negeri Semarang, 2022)
This study wants to examine various factors that affect budget performance, especially in the Faculty of Social Sciences, Universitas Negeri Semarang through Goal Setting Theory. The data used in this study is primary data. This data is data directly obtained from respondents by distributing questionnaires to implementers of work activities within the Faculty of Social Sciences, Universitas Negeri Semarang to determine the effect of the Variable Fund Withdrawal Plan and HR Competence on Budget Performance Mediated by Budget Absorption at the Faculty of Social Sciences. Unnes. Determination of the sample is based on what is suggested by Hair et al., (2010) that is, 5-10 times the number of research indicators. In this study there were 23 indicators, so in this study the sample used was 138 people.